ANALISA KONDISI FUNGSIONAL JALAN DENGAN METODE SURVEI VISUAL, PSI DAN RCI SERTA ANALISA SISA UMUR LAYAN JALAN PADA RUAS JALAN SINDANGLAYA KOTA BANDUNG - Faris Musyafa; Yudi Sekaryadi; Edward Hafudiansyah (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
Sindanglaya Road is a national road in the Bandung that connects the economy between national activity centers, namely the Greater Bandung urban area. So it is necessary to have a road that has good service conditions with a service life that is in accordance with the plan. This study aims to determine the value of the functional condition of the pavement using visual methode, the PSI and RCI methods, as well as to determine the analysis of the remaining service life of the road. In the analysis of the functional condition of the Sindanglaya road using IRI data from Balai Besar Pelaksanaan Jalan dan Jembatan DKI Jakarta-Jawa Barat. The IRI data is correlated with the PSI value to obtain the road service function and the RCI to obtain the road surface condition. Meanwhile, the analysis of the remaining service life used the AASHTO 1993 method using traffic data. Based on the calculations, it was obtained that the functional condition of the Sindanglaya Road shows that the average service function of the road is less, with a PSI value of 4.99 and for the visual condition of the road surface it is very good, generally flat with an RCI value of 7.007. The results of the analysis of road service life on the Sindanglaya Road section show that the service life of the road will end in 2028 or 3 years faster than the final plan in 2031, where there is a decrease in road service life of 13,952 %.